PEMETAAN DAN VALUASI EKONOMI KERUGIAN BANJIR DI KARESIDENAN SURAKARTA - ., Suryanto (PIRAMIDA, 2017)
Negative impact of Cilmate change as current environmental issues could not be avoided. Climate change caused loss especially for agricultural sector. The purposes of research: 1) to mapping and identify flooding area, 2) to estimate negative loss of climate change to decreasing of farm production and farmer income. This study used quantitative approfach to estimate probability loss in agricultural land. Tool of analysis to mapping and identify the vulnerable area relied on Geographic Information. Spatial data would be needed in this research to give information about the area. Economic valuation would give result value loss of production caused of climate change impact. Result of data analysis showed that most of regencies in Karesidenan Surakarta have vulnerable area of flood. These regencies were Kota Surakarta, Kabupaten Sragen, Karanganyar, Sukoharjo, and Klaten. The other regencies such as Boyolali and Wonogiri could be classified as less vulnerable to flood hazard. Based on economic valuation gave result that 36.72 percent to total of agricultural land vulnerable toward flood and 24.55 percent to total of agricultural land vulnerable toward drought.